Effect Analysis of Geometric Parameters on Stainless Steel Stamping Multistage Pump by Experimental Test and Numerical Calculation - Chuan Wang; Weidong Shi; Ling Zhou; Weigang Lu (Advances in Mechanical Engineering, 2013)
In order to improve the efficiency of stainless steel stamping multistage pump, quadratic regression orthogonal test, hydraulic design, and computational fluid dynamics (CFD) are used to analyze the effect of pump geometric parameters. Sixteen impellers are designed based on the quadratic regression orthogonal test, which have three factors including impeller outlet slope, impeller blade outlet stagger angle, and impeller blade outlet width. Through quadratic regression equation, the function relationship between efficiency values and three factors is established. The optimal combination of geometric parameters is found through the analysis of the regression equation. To further study the influence of blade thickness on the performance of multistage pump, numerical simulations of multistage pump with different blade thicknesses are carried out. The influence law of blade thickness on pump performance is built from the external characteristics and internal flow field. In conclusion, with the increase of blade thickness, the best efficiency point of the pump shifts to the small flow rate direction, and the vortex regions inside the pump at rated flow gradually increase, which is the main reason that pump efficiency decreases along with the increase of the blade thickness at rated flow.